Comparative Antioxidant and Anti-Inflammatory Activity of Ellagic Acid and Juglans regia L. in Collagenase-Induced Osteoarthritis in Rats - Alina Hanga-Farcas; Luminita Fritea; Gabriela Adriana Filip; Simona Clichici; Laura Gratiela Vicas; Adina Frum; Mariana Eugenia Muresan (Applied Sciences)
Osteoarthritis (OA), the most common degenerative pathology of the joints, affects mainly elderly people, and it is one of the most important factors causing disability. This study aimed to assess the effect of Juglans regia L. on rats with collagenase-induced knee osteoarthritis comparative with groups with the same disease treated with ellagic acid (EA), indomethacin as positive control and vehicle as negative control. After 2 and 4 weeks of treatment, blood samples were collected in order to evaluate the oxidative stress and inflammation, as well as RANKL and hydroxyproline levels. The results showed that EA improved the systemic antioxidant defense (p < 0.05), decreased the interleukin-6 (IL-6) secretion (p < 0 < 0.05) and RANKL levels (p < 0.01 and p < 0.001) at the same time enhancing hydroxyproline values, particularly after 2 weeks of treatment (p < 0.01). JR extract especially maintained low values of RANKL (p < 0.05) and hydroxyproline levels (p < 0.05), indicating a partial chondroprotective effect compared to EA. In conclusion, the use of EA and JR extract can improve some parameters of bone regeneration in experimental osteoarthritis, suggesting beneficial effects in articular inflammatory diseases. However, further studies are necessary to establish the optimum dose and time of treatment with both compounds in order to obtain optimal therapeutic results.